Status of Montivipera bulgardaghica (Werner, 1898) (Reptilia: Viperidae) in the Syrian Coastal Mountains. Issue 3 (3rd July 2021) - Ahmad, Muhammad; Mebert, Konrad; AlMasri, Aroub; Ibrahim, Nahla
Abstract : A herpetological survey in the Syrian coastal region revealed more than 25 specimens of mountain vipers, genus Montivipera. Environmentally surprising are new records below 6QQ m elevation on both sides (west and east) of the Syrian coastal mountain range. Morphological characters of size and colour pattern corroborate previous genetic results that relate Syrian coastal mountain vipers closer to M. bulgardaghica from southern Turkey than to M. bornmuelleri from the mountains of adjacent Lebanon and Mt. Hermon. The new records not only confirm the historic and only known location near Slanfah, but also extend the distribution considerably, approaching current borders with Turkey in the north and Lebanon in the south. The new records are discussed in respect to morphology, habitat with climate associations, and conservation.